Ploughing depth stability with front plough without support wheel (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
Then aggregating a front plow, an important aspect is ensuring the stability of the plowing depth. This issue becomes especially relevant if this implement does not have a support wheel. In view of this, the purpose of this article is to find out the influence of the operation of a front plow without a support wheel on the stability of the depth of soil cultivation by a plowed machine-tractor unit according to the "push-pull" scheme. Plowing was carried out by two units. One of them (option 1) had a front plow with a support wheel, and the other (option 2) had one without it. Laboratory and field studies revealed that the null hypothesis about the equality of the average values of plowing depth in the compared units is not rejected. The proof of this is the НІР05 of this statistical indicator, which is equal to 0.81 cm, which is greater than the real difference between the compared values of the plowing depth, which is 0.50 cm. It follows that the removal of the support wheel from the front plow does not lead to a significant change in the average value of the plowing depth. On the other hand, the null hypothesis about the equality of the compared variances of the plowing depth fluctuations by plowing aggregates of both options is rejected at the statistical significance level of 0.05. According to the obtained data, the actual significant Fisher's F-test at 1.69 is greater than the tabulated one, which is 1.39. In view of this, it can be stated that the use of a front plow (option 2) leads to a decrease in the dispersion of plowing vibrations in comparison with a plow unit equipped with a front plow with a support wheel (option 1). The process of fluctuating the plowing depth in MTA with a front plow without a support wheel is more low-frequency than a similar process in a plow unit with a front plow tool equipped with a support wheel. This is evidenced by both the course of the normalized spectral densities of the fluctuations of the compared dispersions and the coefficients of variation of the fluctuations of the tillage depth.
Keywords: arable unit; longitudinal field profile; fluctuations; dispersion; normalized correlation function; normalized spectral density